ISOLASI, IDENTIFIKASI, DAN UJI AKTIVITAS ANTIBAKTERI BAKTERI ENDOFIT DARI JAMUR SHIITAKE (Lentinula edodes) DAN JAMUR KUPING HITAM (Auricularia polytricha) TERHADAP BAKTERI PATOGEN DARI PLAK GIGI - Inneke Andita Putri Laoli; Ida Indrawati (Gunung Djati Conference Series, 2021)
Mushrooms contain bioactive compounds that can be used as antibacteria. Like plants, fungi are also associated with several microbes (especially bacteria that can help fungal growth), known as endophytes, to aid in their growth. Endophytic bacteria are bacteria that live in the tissue of its host. Endophytic bacteria can live and grow in Edible mushrooms. The presence of endophytic bacteria in fungi can also help produce bioactive compounds that can act as antibacterial. This study aims to obtain information on endophytic bacterial isolates from shiitake and black ear mushrooms which have the greatest potential to inhibit the growth of pathogenic bacteria. The method used is a descriptive explorative method based on observational data by exploring and taking samples of shiitake mushroom (Lentinula edodes) and black ear mushroom (Auricularia polytricha), sample isolation, gram staining to identify types of bacteria, and then tested for antibacterial activity using the method Kirby-Bauer diffusion. The results showed that endophytic bacteria from shiitake fungus and black ear fungus could inhibit the growth of both types of dental plaque bacteria with the largest average inhibition zone of 10 mm and 7.2 mm against Streptococcus sp. while for Bacillus sp. 9 mm and 8.5 mm. The results of identification of endophytic bacteria using Gram staining showed that the potential endophytic bacteria isolates were JST-1C (Gram-positive bacil) and JKP-1B (Gram-negative bacil).